C-reactive protein as a biomarker of severe H1N1 influenza - Vasileva, Denitsa (Inflamm Res, 2018)
BACKGROUND: C-reactive protein (CRP) is an acute-phase reactant downstream of the pro-inflammatory cytokines released during influenza infection. However, the role of this inflammatory marker in influenza severity and complications is yet to be elucidated. OBJECTIVES: We aim to systematically review and evaluate the levels of CRP in severe and non-severe H1N1 influenza cases and assess its utility as a biomarker in predicting the severity of infection. METHODS: We conducted a comprehensive search in Ovid MEDLINE, Ovid MEDLINE (R) Epub ahead of Print, Embase and Embase Classic to identify human studies reporting measurements of CRP levels in patients infected with H1N1 influenza at various levels of disease severity. RESULTS: Our search identified ten studies eligible for inclusion in this systematic review. The results of the data analysis show that the average CRP levels upon diagnosis were significantly higher (P < 0.05) in patients who developed severe H1N1 influenza compared to their counterparts with a no severe disease. Furthermore, levels of CRP were associated with the degree of H1N1 severity. Subjects with H1N1-related pneumonia and patients who were hospitalized or died of the disease complications, respectively, had 1.4- and 2.5-fold significantly higher CRP levels (P < 0.05) than those with no severe disease outcome. CONCLUSION: CRP levels have been consistently shown to be significantly higher in H1N1 influenza patients who develop a severe disease outcome. The resuts of the present study suggest that serum CRP can be employed—in combination with other biomarkers—to predict the complications of H1N1 influenza. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00011-018-1188-x) contains supplementary material, which is available to authorized users.